Serum autoantibodies and the diagnosis of type-1 autoimmune hepatitis in Italy: a reappraisal at the light of hepatitis C virus infection. Issue 9 (September 1992) - Cassani, F; Muratori, L; Manotti, P; Lenzi, M; Fusconi, M; Ballardini, G; Selleri, L; Volta, U; Zauli, D; Miniero, R
Abstract : Antinuclear antibodies with the homogeneous pattern (ANA-H) and smooth muscle antibodies with antiactin specificity (SMA-AA) are regarded as the serum markers of type-1 autoimmune chronic hepatitis. Their diagnostic relevance, however, has been questioned recently after the detection of signs of hepatitis C virus infection in autoimmune chronic hepatitis patients. To further evaluate this point, antihepatitis C virus antibodies were sought by two second generation assays (ELISA 2 and RIBA 2) in 100 Italian patients with chronic liver disease of unknown aetiology, including 46 with (autoimmune chronic hepatitis) and 54 without the above antibodies (cryptogenic). By ELISA 2, antihepatitis C virus, although significantly prevalent in cryptogenic (83%), were found also in a substantial proportion of autoimmune chronic hepatitis patients (46%) (p < 0.0001), their occurrence was confirmed by RIBA 2 in almost all cases (96% and 86%, respectively). Autoimmune patients with either ANA-H or SMA-AA exhibited similar antihepatitis C virus prevalences (59% and 52%, respectively); by contrast, the eight cases positive for both the autoantibodies were consistently antihepatitis C virus negative. These findings confirm that in countries with high hepatitis C virus circulation (like Italy) an overlap between autoimmune chronic hepatitis and hepatitis C virus infection, reflected by 'true' antihepatitis C virus antibodies, does occur. The detection of ANA-H or SMA-AA, in fact, identifies chronic liver disease patients with a relatively low prevalence of antihepatitis C virus, but does not exclude hepatitis C virus infection. Positive findings for both ANA-H and SMA-AA, however, is an appropriate marker for hepatitis C virus free 'primary' autoimmune chronic hepatitis.